Resolving chronic ear pain by focused extracorporeal shockwave therapy treatment of the temporomandibular joint and the auriculotemporal nerve: A case report - Jorgensen, Jens Erik (Indian Journal of Case Reports, 2025)
This case report aims to describe how the application of focused extracorporeal shockwave therapy to the temporomandibular joint (TMJ) and the auriculotemporal nerve effectively resolved chronic ear pain in a patient treated at a private physiotherapy practice. To the best of the author’s knowledge, this procedure has not been previously reported for this rare condition. Auriculotemporal neuralgia is characterized by acute, unilateral pain in the temporal region, along with nerve sensitivity. The condition may coincide with temporomandibular disorders or present as nerve entrapment, and it is more commonly observed in women. Currently, no standardized treatment protocol exists for this condition. The patient suffered from outer ear pain for approximately 14 years, underwent treatment with focused shockwave therapy at a dosage of 1000–1500 shocks at a frequency of 8 Hz, with an intensity of 0.02–0.1 mJ/mm2, adjusted according to the patient’s pain tolerance. The patient was treated once a week for 3 weeks. The patient experienced resolution of pain after three sessions. These findings suggest that focused shockwave therapy may serve as a viable alternative method for addressing auriculotemporal neuralgia. Further research is warranted to evaluate the efficacy of this approach in a larger cohort.